Individual-, Household-, and Community-Level Determinants of Childhood Undernutrition in Bangladesh - Moriam Khanam; Shafiun N. Shimul; Abdur Razzaque Sarker (SAGE Publishing, 2019)
Introduction: Childhood undernutrition is a crucial public health problem globally. The objective of this study is to measure the prevalence of childhood undernutrition and assess the distinct role of various factors on childhood undernutrition in Bangladesh. Methods: This study utilized the latest cross-sectional data from Bangladesh Demographic and Health Survey 2014. A total of 7256 data on children younger than 5 years old were analyzed. The undernutrition status of children was assessed by stunting (height-for-age), wasting (weight-for-height), and underweight (weight-for-age), while bivariate and multivariate analyses were performed to identify various individual-, household-, and community-level factors of childhood undernutrition. Results: The prevalence of stunting, wasting, and underweight were 36.5%, 14.6%, and 32.5%, respectively. Along with various individual- and household-level factors (eg, age, recent diarrheal disease, fever, number of under-5 children in the household, mother's education and nutritional status, and wealth status), community index, particularly regional and geographic variation of community, had significant role for childhood undernutrition in Bangladesh. Conclusion: Childhood undernutrition is an overwhelming public health issue in Bangladesh. In order to improve the nutritional status of under-5 children, interventions should take into account the various predictors discussed in this study. Indeed, a joint effort by the government, nongovernmental organizations, and the community is necessary to improve the childhood nutritional status in Bangladesh.